Amino functionalized boron nitride and enhanced thermal conductivity of epoxy composites via combining mixed sizes of fillers. Issue 2 (15th January 2022) - Wang, Wei; Zhao, Man; Jiang, Dayong; Zhou, Xuan; He, Jiaqi
Abstract: With the emergence of 5G communication and the rapid development of the microelectronics industry, the heat dissipation of high power circuits has become quite an important issue. Along these lines, the thermal conductivity distribution of the electronic packaging materials, which plays a key role in the protecting circuits, requires urgent improvement. In this study, amino-functional boron nitride nanosheets (BNNS) were prepared by employing ball milling boron nitride with urea (aqueous solution) as agents. Then, the epoxy composites filled with large size pristine boron nitride (pBN) and small size functional boron nitride were fabricated by using the wet ball-milling (wBN) technique. The acquired results indicate that the thermal conductivity property of the pBN/wBN/epoxy composites with pBN/wBN ratio of 2.5/7.5 can reach the value of 0.386 W/mK, which is 96% higher than that of pure epoxy. Meanwhile, the measured value is superior from both the pBN/epoxy and wBN/epoxy composites with the same filling amount. This effect can be attributed to the efficient construction of the fillers network and thermal conduction path. Within the epoxy matrix, wBN can fill the pores between pBN and form a denser filler network. In addition, the amino-functional groups grafted with wBN result in their enhanced dispersion within the epoxy matrix that leads to a more stronger interfacial effect. Our approach provides useful insights in understanding the incorporation mechanisms of fillers in polymers, and thereby enhancing their potential applications.